Corporate Social Responsibility: Ranking Public Listed Companies in Malaysia - Irma Yazreen, Md Yusoff; Lau, Sim Yee (Reitaku International Society of Economic Studies, 2016)
This study formulates a CSR index―which is a multi-dimensional metric―for assessing the performance of corporate social responsibility (CSR) of the Top100 PLCs in market capitalization in the Bursa Malaysia. Data on financial performances of these companies in 2012 were sourced from Thompson DataStream whilst other CSR related components were taken from each company’s annual report and sustainability report that are available in public domain. CSR index of each Top 100 PLCs was computed by unweighted and weighted methods. This result shows that Public Bank is strongly balanced in profit generation and CSR contribution. The findings also show the rankings of some PLCs have improved when CSR activities with the assigned weightage are incorporated as moderators for evaluating CSR performances. The opposite results were also evident from the analysis. More importantly, the results suggest that with an appropriate system of metrics in quantifying CSR performances, a corporation could certainly achieve a better standing in the society not merely due to a better financial performance but because of its strive to becoming a more responsible corporate citizen in enhancing social wellbeing beyond the acts of paying taxes, employment generation and maximization of shareholders wealth. Hence CSR activities should not be viewed as a means for improving public and investment relations but they ought to be included as an integral part of the corporate’s role in the society.